Speech Acts Directive and Strategy Indonesian Language Teachers in Learning in Class VII of Smp Negeri 2 Kinali - Yulina Wisna Jaya; Ngusman Abdul Manaf; Novia Juita (Postgraduate School, Universitas Negeri Padang, 2020)
This research is backed by the problem of frequent misunderstandings between students and teachers. The misunderstanding occurs because students are less able to understand the intent and purpose that the teacher delivered. The purpose and objectives of the teacher cannot be well received by the students because of the form and strategy used by the teacher less according to the situation and condition when said. This research was conducted to explain the follow-up and strategy to speak Indonesian teachers in the learning process in SMP Negeri 2 Kinali. This type of research is a qualitative study with a descriptive method. Data collection is conducted through observation and recording of two Indonesian teachers who teach in class VII SMP Negeri 2 Kinali. The research Data is analyzed qualitatively based on the speech theory. The results of this study are as follows. First, the type of follow-up directive found was (1) to ask, (2) to have, (3) Beg, and (4) advise. The Act of Directive, which is dominant by Indonesian teachers, is that the teacher and the least used by the teachers is a follow-up directive. Secondly, the said strategy used to realize the follow-up directive in the learning process in class VII SMP Negeri 2 Kinali is (1) The strategy is frankly without further ado, (2) The strategy is frankly with positive civility, (3) The strategy is straightforward with a negative silence, and (4) a vague strategy. The strategy says frankly without the dominant unpleasantness teachers used in the learning process on the kind of follow-up said.